PROTOTYPE SISTEM KUNCI PINTU BERBASISQRCODE DAN ARDUINO - Prakasa, Gifari Alim, Aris Rakhmadi, S.T., M. Eng (2017)
The security system of door lock at house today mostly a manual security system like conventional key or padlock. The research aims to create an alternative prototype security system on the door lock of house by utilizing technology and low costs. This research uses an Arduino as a microcontroller driving solenoid, and Android as a controller of Arduino and QR Code reader. Arduino programming using the Arduino IDE (Integrated Development Environtment). QR Code reader on Android created with App Inventor. Android and Arduino will be connected with bluetooth IEE 802.15. Research testing do with different versions of Android, that is Jelly bean 4.1.2, Lollipop 5.0.1 and Marshmallow 6.0.1. Testing shows all hardware and software components can work well. This research resulted in Smart door lock which is cheaper than Smart door locks are sold today.